EVALUASI PENGGUNAAN OBAT ASMA PASIEN RAWAT JALAN DI RUMAH SAKIT TK. IV. 01.07.01 PEMATANGSIANTAR PERIODE APRIL - JUNI TAHUN 2024 - Almazhia Mahliza; Elia Haloho; Emi Sugesti (CV. ADIBA ADISHA AMIRA, 2024)
Asthma is a chronic disease of the respiratory tract characterized by inflammation, increased reactivity to various stimuli, and airway narrowing that can return spontaneously or if taking appropriate medication. Data from the Word Health Organization in 2019 stated that the number of asthma sufferers in the world reached 300 million people causing morbidity together with chronic bronchitis. This study is a type of observational study using a descriptive research design with retrospective data collection on ASMA patients at Tk. Iv Hospital. 01.07.01 Pematang Siantar. This study aims to evaluate the use of drugs in ASMA patients at Tk. Iv Hospital. 01.07.01 Pematang Siantar. The samples of this study were ASMA patient prescriptions and medical records. Recipes that will be examined are matched with medical records. The data obtained were processed with the Ms Excel computer system and then presented in a frequency distribution. Based on the results of the research conducted, the results of the evaluation of the accuracy of drug use in asthma patients, namely the right drug 96 patients reached 100%, the right patient 96 patients reached 100%, the right indication96 patients reached 100%, the right dose 96 patients reached 100% and the right method of administration 96 patients reached 100%. evaluation of the use of asthma drugs obtained 2 types of asthma drug classes, namely bronchodilators and corticosteroids.